When you don't start at 1

Algebra Level 3

It is fairly well-known that ( 1 + 2 + 3 + . . . + ( n 1 ) + n ) 2 1 3 + 2 3 + 3 3 + . . . + ( n 1 ) 3 + n 3 \left(1+2+3+...+(n-1)+n \right)^2 \equiv 1^3 + 2^3 + 3^3 + ... + (n-1)^3 + n^3

However, how many pairs of positive integers a , b a,b where b > a b>a and a 1 a \neq 1 are there such that the following holds? ( a + ( a + 1 ) + ( a + 2 ) + . . . + ( b 1 ) + b ) 2 a 3 + ( a + 1 ) 3 + ( a + 2 ) 3 + . . . + ( b 1 ) 3 + b 3 \left(a + (a+1) + (a+2) + ... + (b-1) + b \right)^2 \equiv a^3 + (a+1)^3 + (a+2)^3 + ... + (b-1)^3 + b^3

There are no other pairs There are finitely many other pairs There are infinitely many other pairs

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chris Lewis
May 22, 2019

For positive integer n n , define T n = 1 + 2 + + n T_n = 1+2+\cdots + n and C n = 1 3 + 2 3 + + n 3 C_n = 1^3+2^3+\cdots + n^3 .

The identity we're given at the start is C n = T n 2 C_n=T_n^2 , which holds for all n n .

To neaten up the notation, put c = a 1 c=a-1 . We're told c > 0 c>0 .

The equation can then be written as

( T b T c ) 2 = C b C c = T b 2 T c 2 (T_b-T_c)^2=C_b-C_c=T_b^2-T_c^2

Since b > a > c b>a>c we can divide through by T b T c T_b-T_c to give

T b T c = T b + T c T_b-T_c=T_b+T_c

which can only happen when T c = 0 T_c=0 ; but this is impossible, since c > 0 c>0 ; so there are no other pairs of positive integers that satisfy the equation.

Chew-Seong Cheong
May 22, 2019

The LHS \text{LHS} of the last "equation" can be expressed as:

S = ( k = a b k ) 2 = ( k = 1 b k k = 1 a 1 k ) 2 = ( k = 1 b k ) 2 2 k = 1 b k k = 1 a 1 k + ( k = 1 a 1 k ) 2 = k = 1 b k 3 2 k = 1 b k k = 1 a 1 k + k = 1 a 1 k 3 \begin{aligned} S & = \left(\sum_{k=a}^b k \right)^2 \\ & = \left(\sum_{k=1}^b k - \sum_{k=1}^{a-1} k \right)^2 \\ & = \left(\sum_{k=1}^b k \right)^2 - 2\sum_{k=1}^b k \sum_{k=1}^{a-1} k + \left(\sum_{k=1}^{a-1} k \right)^2 \\ & = \sum_{k=1}^b k^3 - 2\sum_{k=1}^b k \sum_{k=1}^{a-1} k + \sum_{k=1}^{a-1} k^3 \end{aligned}

If LHS = RHS \text{LHS} = \text{RHS} , then

k = 1 b k 3 2 k = 1 b k k = 1 a 1 k + k = 1 a 1 k 3 = k = a b k 3 = k = 1 b k 3 k = 1 a 1 k 3 k = 1 b k k = 1 a 1 k = k = 1 a 1 k 3 \begin{aligned} \sum_{k=1}^b k^3 - 2\sum_{k=1}^b k \sum_{k=1}^{a-1} k + \sum_{k=1}^{a-1} k^3 & = \sum_{k=a}^b k^3 \\ & = \sum_{k=1}^b k^3 - \sum_{k=1}^{a-1} k^3 \\ \implies \sum_{k=1}^b k \sum_{k=1}^{a-1} k & = \sum_{k=1}^{a-1} k^3 \end{aligned}

The above equation holds true only when b = 1 b=1 and a = 2 a=2 , which contradicts with the assumption of b > a b>a . Therefore, there are no other pairs of ( a , b ) (a,b) that the equation holds.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...